The biology and ecology of the trunk borer Coryphodema tristis (Drury) on grapevines - Hoppner, Gerd Fritz Jurgen (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1991.